RELASI GENDER DALAM HADIST: STUDI ATAS INTERAKSI MAHASIWA LAKI LAKI DAN PEREMPUAN: Pola Penafsiran Hadis oleh Mahasiswa, Legitimasi Relasi Kuasa dalam Interaksi Akademik, Pola Interaksi Sosial di Lingkungan Kampus, Posisi Otoritas Perempuan dalam Kepemimpinan Kampus - M. Nuzulul Ulum; Marhumah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze gender relations in the interactions between male and female students on campus by referring to the interpretation of hadiths and the accompanying social dynamics. The method used is descriptive qualitative through observation, in-depth interviews, and documentation. Data analysis was carried out using Fatema Mernissi’s theoretical approach, which emphasizes criticism of patriarchal structures and the authority of hadith interpretation. The results of the study show that there are two patterns of hadith interpretation among students, namely textual and contextual. Textual interpretation tends to be used to legitimize hierarchical divisions of social roles and to position men as leaders, while contextual interpretation encourages equality and collaborative relations in both academic and organizational interactions. Social interaction on campus also shows the existence of spatial separation and restricted communication that is internalized especially among women, influenced by cultural norms and uncritical religious understanding. However, there are also spaces of resistance through female leadership that is dialogical and collaborative. This study affirms the importance of strengthening contextual hadith literacy and establishing an inclusive campus culture as steps toward just and equal gender relations.